Process for the production of thermoplastic elastomer compositions
Patent Information
- Application Number
- CN202211011803.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-26
- Filing Date
- 2022-08-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-08-23
AI Technical Summary
[0058]根据本发明的制造方法,能够得到以高水平兼具优异的外观和刚性的成型体,并且能够制造能够适合用于安全气囊容纳罩等各种用途的热塑性弹性体组合物。
Smart Images

Figure CN115922937B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to thermoplastic elastomer compositions. Background Technology
[0002] A thermoplastic elastomer composition comprising propylene resins and ethylene-α-olefin-nonconjugated diene copolymer rubber is used as a material for the airbag containment (see, for example, Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-224837 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] The key requirements for airbag housings include excellent appearance and high rigidity. Because the passenger-side airbag housing is larger than the driver-side airbag housing, higher rigidity is required, necessitating a balance between appearance and rigidity at an even higher level.
[0008] In this context, the problem to be solved by the present invention is to provide a method for manufacturing a thermoplastic elastomer composition that can produce a molded body with both excellent appearance and rigidity at a high level.
[0009] means for solving problems
[0010] Given this background, the inventors conducted in-depth research and, as a result, completed this invention.
[0011] That is, the present invention is: [1]
[0013] A method for manufacturing a thermoplastic elastomer composition, wherein the method comprises the following first and second steps, and the content of mineral oil (C) in the manufactured thermoplastic elastomer composition is 5% by mass or less.
[0014] First step: A step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of organic peroxides, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g;
[0015] The second step: Further addition of polypropylene (A-2) and melt mixing, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C... cxisThe value is above 1.5 dl / g and below 7 dl / g.
[0016] Hereinafter, [2] to
[19] are each preferred embodiments or implementations of the present invention. [2]
[0018] The method for manufacturing a thermoplastic elastomer composition as described in [1], wherein the second step is carried out under conditions in which the organic peroxide is substantially absent. [3]
[0020] A method for manufacturing a thermoplastic elastomer composition as described in [1] or [2], wherein the same extruder with a plurality of feed ports is used in the first and second steps, and polypropylene (A-2) is supplied from a feed port located further downstream. [4]
[0022] A method for manufacturing a thermoplastic elastomer composition as described in any one of [1] to [3], wherein, in the second step, 0.1 to 15 parts by mass of polypropylene (A-2) are supplied relative to a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B). [5]
[0024] A method for manufacturing a thermoplastic elastomer composition as described in any one of [1] to [4], wherein 30 to 70 parts by mass of polypropylene (A-1) and 70 to 30 parts by mass of ethylene copolymer rubber (B) are supplied based on a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B). [6]
[0026] The method for manufacturing a thermoplastic elastomer composition as described in any one of [1] to [5], wherein at least a portion of the ethylene copolymer rubber (B) is an amorphous ethylene-α-olefin copolymer (B1-1) or an ethylene-α-olefin-nonconjugated diene copolymer (B1-2). [7]
[0028] A thermoplastic elastomer composition, wherein the thermoplastic elastomer composition is manufactured by a manufacturing method comprising the first step and the second step described below, and the mineral oil (C) content in the thermoplastic elastomer composition is 5% by mass or less.
[0029] First step: A step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of organic peroxides, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g;
[0030] The second step: Further addition of polypropylene (A-2) and melt mixing, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C... cxis The value is above 1.5 dl / g and below 7 dl / g. [8]
[0032] The thermoplastic elastomer composition as described in [7], wherein the second step is carried out in the absence of the organic peroxide. [9]
[0034] Thermoplastic elastomer composition as described in [7] or [8], wherein the same extruder with multiple feed ports is used in the first and second steps, and polypropylene (A-2) is supplied from a feed port located further downstream.
[10]
[0036] The thermoplastic elastomer composition as described in any one of [7] to [9], wherein, in the second step, 0.1 to 15 parts by weight of polypropylene (A-2) are supplied relative to a total of 100 parts by weight of polypropylene (A-1) and ethylene copolymer rubber (B).
[11]
[0038] The thermoplastic elastomer composition as described in any one of [7] to
[10] , wherein 30 to 70 parts by mass of polypropylene (A-1) and 70 to 30 parts by mass of ethylene copolymer rubber (B) are supplied based on a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B).
[12]
[0040] The thermoplastic elastomer composition as described in any one of [7] to
[11] , wherein at least a portion of the ethylene copolymer rubber (B) is an amorphous ethylene-α-olefin copolymer (B1-1) or an ethylene-α-olefin-nonconjugated diene copolymer (B1-2).
[13]
[0042] The thermoplastic elastomer composition as described in any one of [7] to
[12] , wherein the thermoplastic elastomer composition is used for injection molding.
[14]
[0044] The thermoplastic elastomer composition as described in any one of [7] to
[13] , wherein the injection is carried out at a barrel temperature of 220°C, a mold temperature of 50°C, and an injection rate of 25 cm. 3Under the condition of / second, the thermoplastic elastomer composition described in any one of [7] to
[13] is injection molded to obtain a molded body with a width of 90 mm × length of 150 mm × thickness of 2.0 mm, and the flexural modulus obtained by measuring the molded body according to JIS K7171 is 330 MPa or more.
[15]
[0046] A molded body comprising any one of the thermoplastic elastomer compositions described in [7] to
[14] .
[16]
[0048] The molded body as described in
[15] has a flexural modulus of 330 MPa or more as measured according to JIS K7171.
[17]
[0050] The molded body as described in
[15] or
[16] , wherein the molded body is an uncoated molded body.
[18]
[0052] The molded body as described in any one of
[15] to
[17] is an airbag containment cover.
[19]
[0054] A method for manufacturing a molded article containing a thermoplastic elastomer composition, wherein the manufacturing method includes a step of mixing a thermoplastic elastomer composition precursor and polypropylene (A-2) and molding them.
[0055] The intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C cxis The concentration is above 1.5 dl / g and below 7 dl / g.
[0056] The thermoplastic elastomer composition precursor is manufactured by a manufacturing method comprising a step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of an organic peroxide, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g.
[0057] Invention Effects
[0058] According to the manufacturing method of the present invention, it is possible to obtain molded articles with both excellent appearance and rigidity at a high level, and to manufacture thermoplastic elastomer compositions suitable for various applications such as airbag housings. Attached Figure Description
[0059] Figure 1 This is a diagram showing the molded body used in the appearance evaluation of the embodiments. Detailed Implementation
[0060] The method for manufacturing the thermoplastic elastomer composition of the present invention comprises the following first and second steps, and the thermoplastic elastomer composition produced contains a mineral oil (C) content of 5% by mass or less.
[0061] First step: A step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of organic peroxides, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g;
[0062] The second step: Further addition of polypropylene (A-2) and melt mixing, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C... cxis The value is above 1.5 dl / g and below 7 dl / g.
[0063] That is, in the method for manufacturing the thermoplastic elastomer composition of the present invention, the intrinsic viscosity [η] of the xylene-insoluble component at 20°C is used. cxis The intrinsic viscosity [η] of polypropylene (A-1) with an intrinsic viscosity greater than or equal to 0.1 dl / g and less than 1.5 dl / g at 20℃ for the xylene-insoluble component. cxis The starting materials are polypropylene (A-2) with a concentration of 1.5 dl / g or higher and 7 dl / g or lower, ethylene copolymer rubber (B), and organic peroxides. Mineral oil (C) can also be used as an optional component.
[0064] The following is an explanation of each of the above components.
[0065] Intrinsic viscosity of xylene-insoluble components at 20℃ [η] cxis Polypropylene with a concentration greater than or equal to 0.1 dl / g and less than 1.5 dl / g Alkene (A-1)
[0066] In the method for manufacturing the thermoplastic elastomer composition of the present invention, the polypropylene (A-1) used as the starting material is a (co)polymer in which the content of structural units derived from propylene is greater than 50% by mass and less than or equal to 100% by mass.
[0067] The difference between polypropylene (A-1) and the ethylene copolymer rubber (B) described later is that the content of propylene-derived structural units is greater than 50% by mass.
[0068] The intrinsic viscosity [η] of polypropylene (A-1) and the xylene-insoluble component at 20°C (described later) cxis The difference between polypropylene (A-2) with a viscosity of 1.5 dl / g or higher and 7 dl / g or lower lies in the intrinsic viscosity [η] of the xylene-insoluble component at 20°C. cxis] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g.
[0069] Here, the intrinsic viscosity [η] of the xylene-insoluble component at 20℃ is... cxis The intrinsic viscosity [η] is obtained by measuring the portion of xylene (hereinafter also referred to as the CXIS portion) that is insoluble in xylene at 20°C, obtained by the method described below, using the method described later.
[0070] 5g of polypropylene (A-1) was completely dissolved in 500ml of boiling xylene. The resulting xylene solution was slowly cooled to 20°C and allowed to settle at 20°C for at least 4 hours. The precipitate was then separated from the solution by filtration. This precipitate was the CXIS fraction.
[0071] It should be noted that the substance obtained by removing the solvent from this solution is the CXS fraction (the xylene-soluble fraction at 20°C), and the intrinsic viscosity of the CXS fraction will also be recorded below as [η]. cxs ].
[0072] [η] of polypropylene (A-1 cxs Preferably, the [η] is 0.1 dl / g or more and 8.0 dl / g or less, more preferably 0.3 dl / g or more and 7.0 dl / g or less. Furthermore, the [η] of polypropylene (A-1) cxs ] relative to [η cxis The ratio of η cxs ] / [η cxis Preferably, the value is 0.01 or higher and 12.0 or lower, more preferably 0.05 or higher and 11.0 or lower.
[0073] The intrinsic viscosity was determined using the following steps. The specific viscosity was measured in tetrahydronaphthalene at 135°C using an Ubbelohde viscometer. The intrinsic viscosity was then calculated by extrapolation from the specific viscosity obtained, following the calculation method described on page 491 of "Polymer Solutions, Polymer Experimentation 11" (published by Kyoritsu Publishing Co., Ltd. in 1982).
[0074] Considering the appearance and tensile strength of the molded product, polypropylene (A-1) with [η] is preferred. cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g.
[0075] [η] of polypropylene (A-1 cxis Preferably, the concentration is greater than or equal to 0.1 dl / g and less than 1.5 dl / g, more preferably greater than or equal to 0.2 dl / g and less than 1.5 dl / g, and even more preferably greater than or equal to 0.3 dl / g and less than 1.5 dl / g.
[0076] [η] of polypropylene (A-1 cxisThe molecular weight, molecular weight distribution, and stereoregularity of polypropylene (A-1) can be appropriately adjusted.
[0077] Examples of polypropylene (A-1) include: propylene homopolymers, propylene random copolymers, and propylene polymers as described below. Polypropylene (A-1) may consist of only one of these components or may be a mixture of two or more. From the viewpoint of the appearance of the molded article, the polypropylene (A-1) used in the first step preferably contains at least a portion of a propylene random copolymer.
[0078] Examples of the above-mentioned random copolymers of propylene include:
[0079] (1) A propylene-ethylene random copolymer in which the content of propylene-derived structural units is 90% or more and 99.5% or less, and the content of ethylene-derived structural units is 0.5% or more and 10% or less (wherein, the total content of propylene-derived structural units and ethylene-derived structural units is set as 100% by mass).
[0080] (2) A propylene-ethylene-α-olefin random copolymer in which the content of structural units derived from propylene is 81% to 99% by mass, the content of structural units derived from ethylene is 0.5% to 9.5% by mass, and the content of structural units derived from α-olefins with 4 to 10 carbon atoms is 0.5% to 9.5% by mass (wherein, the total content of structural units derived from propylene, structural units derived from ethylene, and structural units derived from α-olefins with 4 to 10 carbon atoms is set as 100% by mass); and
[0081] (3) A propylene-α-olefin random copolymer in which the content of structural units derived from propylene is 90% by mass or more and 99.5% by mass or less, and the content of structural units derived from α-olefins having 4 to 10 carbon atoms is 0.5% by mass or more and 10% by mass or less (wherein, the total content of structural units derived from propylene and structural units derived from α-olefins having 4 to 10 carbon atoms is set as 100% by mass).
[0082] Examples of α-olefins with 4 or more but less than 10 carbon atoms in the above-mentioned propylene-ethylene-α-olefin random copolymers and propylene-α-olefin random copolymers include: 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, 2,2,4-trimethyl-1-pentene, etc.
[0083] As a method for manufacturing the aforementioned propylene homopolymer and the aforementioned propylene random copolymer, known polymerization methods using known catalysts for olefin polymerization can be listed, such as slurry polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization using complex catalysts such as Ziegler-Natta type catalysts, metallocene complexes, or non-metallocene complexes.
[0084] Propylene homopolymers can be manufactured in a single polymerization reactor or through multi-step polymerization in a manufacturing apparatus that connects multiple reactors in series. In the case of multi-step polymerization, the intrinsic viscosities of the propylene homopolymers manufactured in the previous step and those manufactured in the next step can be the same or different.
[0085] The aforementioned propylene polymer material is a polymer material comprising a propylene homopolymer portion (I) and an ethylene copolymer portion (II), wherein the ethylene copolymer portion (II) has structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms, and structural units derived from ethylene. The content of the propylene homopolymer portion (I) in this propylene polymer material is 70% by mass or more and 95% by mass or less, and the content of the ethylene copolymer portion (II) is 5% by mass or more and 30% by mass or less. From the viewpoint of low-temperature impact resistance of the molded article, the content of the propylene homopolymer portion (I) in this propylene polymer material is preferably 75% by mass or more and 95% by mass or less, and the content of the ethylene copolymer portion (II) is preferably 5% by mass or more and 25% by mass or less (wherein, the total amount of the propylene polymer material is set to 100% by mass).
[0086] Examples of α-olefins with 4 or more carbon atoms in the ethylene copolymer portion (II) include: 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadecanene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecanene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene. Among these, α-olefins with 4 or more carbon atoms are preferred, those with 4 or more but less than 20 carbon atoms are more preferred, those with 4 or more but less than 10 carbon atoms are more preferred, and 1-butene, 1-hexene, or 1-octene are even more preferred. α-olefins with 4 or more carbon atoms can be used alone or in combination of two or more.
[0087] From the viewpoint of the low-temperature impact resistance of the molded article, the content of ethylene-derived structural units in the ethylene copolymer portion (II) is generally 22% by mass or more and 80% by mass or less, preferably 25% by mass or more and 70% by mass or less, and more preferably 27% by mass or more and 60% by mass or less. From the viewpoint of the low-temperature impact resistance of the molded article, the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the ethylene copolymer portion (II) is generally 20% by mass or more and 78% by mass or less, preferably 30% by mass or more and 75% by mass or less, and more preferably 40% by mass or more and 73% by mass or less (wherein, the total content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms and the content of structural units derived from ethylene are set to 100% by mass). The content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms and the content of structural units derived from ethylene can be determined by infrared spectroscopy.
[0088] Examples of ethylene copolymer portions (II) include propylene-ethylene copolymers, ethylene-(1-butene) copolymers, ethylene-(1-hexene) copolymers, ethylene-(1-octene) copolymers, propylene-ethylene-(1-butene) copolymers, propylene-ethylene-(1-hexene) copolymers, propylene-ethylene-(1-octene) copolymers, etc., with propylene-ethylene copolymers or propylene-ethylene-(1-butene) copolymers being preferred. Ethylene copolymer portions (II) can be random copolymers or block copolymers.
[0089] Propylene polymer materials can be manufactured through multi-step polymerization using a polymerization catalyst. For example, a propylene polymer material can be manufactured by producing a propylene homopolymer portion (I) in a previous polymerization step and an ethylene copolymer portion (II) in a subsequent polymerization step.
[0090] Examples of polymerization catalysts used in the manufacture of propylene polymers include: Ziegler-type catalyst systems; Ziegler-Natta-type catalyst systems; catalyst systems containing transition metal compounds of Group 4 of the periodic table with cyclopentadienyl rings and alkylaluminoxanes; catalyst systems containing transition metal compounds of Group 4 of the periodic table with cyclopentadienyl rings, compounds that form ionic complexes by reacting with the transition metal compounds, and organoaluminum compounds, etc.
[0091] Alternatively, a prepolymerization catalyst can be used in the presence of the aforementioned polymerization catalyst. Examples of prepolymerization catalysts include those described in Japanese Patent Application Publication Nos. 61-218606, 61-287904, 5-194685, 7-216017, 9-316147, 10-212319, and 2004-182981.
[0092] Polymerization methods used in the manufacture of propylene polymeric materials include bulk polymerization, solution polymerization, slurry polymerization, and gas-phase polymerization. Inert hydrocarbon solvents used in solution polymerization and slurry polymerization include propane, butane, isobutane, pentane, hexane, heptane, and octane. Two or more of these polymerization methods can be combined, and they can be either batch or continuous. Continuous gas-phase polymerization and bulk-gas-phase polymerization that continuously performs bulk polymerization and gas-phase polymerization are preferred methods for manufacturing propylene polymeric materials.
[0093] According to JIS K7210, the melt flow rate of polypropylene (A-1) at 230°C and a load of 21.18 N is generally 10 g / 10 min or more and 300 g / 10 min or less. From the viewpoint of tensile strength of the molded body, it is preferred to be 10 g / 10 min or more and 100 g / 10 min or less.
[0094] The isotactic pentamematic fraction of polypropylene (A-1) determined by 13C-NMR is preferably 0.95 or higher, more preferably 0.98 or higher.
[0095] Here, the isotactic pentagonal fraction refers to the fraction of propylene monomer units located at the center of the isotactic chain (counting pentagonal units) in the molecular chain of propylene polymer resins. In other words, it refers to the fraction of propylene monomer units in a chain (hereinafter denoted as mmmm) formed by the continuous meso-racemic bonding of 5 propylene monomer units. The method for determining the isotactic pentagonal fraction is the method described by A. Zambelli et al. in Macromolecules, 6, 925 (1973), namely, the method of determination by 13C-NMR.
[0096] Specifically, the ratio of the area of the NMR peak attributable to mmmm as determined by 13C-NMR spectroscopy to the area of the absorption peak in the methyl carbon region is the isotactic five-unit group fraction.
[0097] The melting temperature of polypropylene (A-1) is typically 100°C or higher. The melting temperature of propylene homopolymers and propylene polymers, which are preferred embodiments of polypropylene (A-1), is preferably 155°C or higher, more preferably 160°C or higher. The melting temperature of propylene random copolymers, another preferred embodiment of polypropylene (A-1), is preferably 130°C or higher, more preferably 135°C or higher. Furthermore, the melting temperature of polypropylene (A-1) is typically 175°C or lower. In this invention, the melting temperature is the peak temperature of the endothermic peak with the largest peak temperature in the differential scanning calorimetry (DSC) curve during a heating operation, as measured using a differential scanning calorimeter. The measurement conditions for the differential scanning calorimetry curve using a differential scanning calorimeter are as follows.
[0098] <Measurement Conditions>
[0099] Cooling operation: Melt polypropylene (A-1) at 220°C, then cool it from 220°C to -80°C at a cooling rate of 10°C / min.
[0100] Heating operation: After cooling from 220℃ to -80℃, immediately heat up from -80℃ to 220℃ at a rate of 10℃ / minute.
[0101] Intrinsic viscosity of xylene-insoluble components at 20℃ [η] cxis Polypropylene (A-) with a concentration of 1.5 dl / g or higher and 7 dl / g or lower. 2)
[0102] In the method for manufacturing the thermoplastic elastomer composition of the present invention, the polypropylene (A-2) used as the starting material is a (co)polymer in which the content of structural units derived from propylene is greater than 50% by mass and less than or equal to 100% by mass. Examples of polypropylene (A-2) include: propylene homopolymers, propylene random copolymers, and propylene polymers as described below. Polypropylene (A-2) may consist of only one (co)polymer or may contain two or more (co)polymers.
[0103] The difference between polypropylene (A-2) and the ethylene copolymer rubber (B) described later is that the content of propylene-derived structural units is greater than 50% by mass.
[0104] The intrinsic viscosity [η] of polypropylene (A-2) and the xylene-insoluble component at 20℃ cxis The difference between polypropylene (A-1) with a viscosity greater than or equal to 0.1 dl / g and less than 1.5 dl / g lies in the intrinsic viscosity [η] of the xylene-insoluble component at 20°C. cxis The intrinsic viscosity is 1.5 dl / g or higher and 7 dl / g or lower. Here, a method for separating the xylene-insoluble fraction (CXIS fraction) and the xylene-soluble fraction (CXS fraction) of polypropylene (A-2) at 20°C, and the intrinsic viscosity [η] are described. cxis ] and [η cxsThe determination method for the intrinsic viscosity [η] of polypropylene (A-1) is related to the determination method for the intrinsic viscosity of polypropylene (A-1). cxis ] and [η cxs The determination method is the same as that described in detail above.
[0105] [η] of polypropylene (A-2 cxis With a content of 1.5 dl / g or more and 7 dl / g or less, by adding the polypropylene (A-2) in the second process and performing melt mixing, a thermoplastic elastomer composition that can produce a molded body with both excellent appearance and rigidity at a high level can be manufactured.
[0106] [η] of polypropylene (A-2 cxis Preferably, the concentration is 1.5 dl / g or more and 7.0 dl / g or less, more preferably 1.7 dl / g or more and 7.0 dl / g or less, and even more preferably 2.0 dl / g or more and 7.0 dl / g or less.
[0107] According to JIS K7210, the melt flow rate of polypropylene (A-2) at 230°C and a load of 21.18 N is generally 0.1 g / 10 min or more and 10 g / 10 min or less. From the viewpoint of the rigidity of the molded body, it is preferred to be 0.1 g / 10 min or more and 8.0 g / 10 min or less.
[0108] Regarding aspects other than those described above, the details of the representative or preferred monomer composition, physical properties, manufacturing methods, etc. of polypropylene (A-2) are the same as those described above for polypropylene (A-1).
[0109] Ethylene copolymer rubber (B)
[0110] In the method for manufacturing the thermoplastic elastomer composition of the present invention, the ethylene copolymer rubber (B) used as the starting material is a (co)polymer with ethylene-derived structural units as the main structural units (50% by mass or more). It is not particularly limited except that it is a substance capable of crosslinking using organic peroxides. Preferably, it is one or more ethylene polymers selected from the group consisting of the amorphous ethylene polymer (B1) described later and a crystalline ethylene copolymer component (B2) with ethylene-derived structural units of 50% to 90% by mass or more. Among these, the amorphous ethylene polymer (B1) is preferred.
[0111] The ethylene copolymer rubber (B) may consist only of the above-mentioned component (B1) or only of component (B2). In addition to the above-mentioned components (B1) and / or component (B2), it may also contain other components.
[0112] There are no particular restrictions on the content of components (B1) and (B2) described later. When the mass of the ethylene copolymer rubber (B) is set to 100% by mass, it is permissible to contain components (B1) of 0% by mass and 100% by mass and components (B2) of 0% by mass and 100% by mass.
[0113] As a method, the content of component (B1) can be 5% by mass or more and 85% by mass or less, and the content of component (B2) can be 15% by mass or more and 95% by mass or less.
[0114] There are no particular limitations except that the ethylene polymer constituting the ethylene copolymer rubber (B) contains more than 50% by mass of structural units derived from ethylene, and preferably one or more ethylene polymers selected from the group consisting of the following components (B1) and (B2).
[0115] Amorphous ethylene polymers (B1)
[0116] The amorphous ethylene polymer (B1) preferably used as all or part of the ethylene copolymer rubber (B) is any ethylene polymer that is derived from ethylene structural units at a rate of 50% or more by mass, can be crosslinked using organic peroxides, and is amorphous at room temperature. Other than these limitations, the amorphous ethylene-α-olefin copolymer (B1-1) and / or ethylene-α-olefin-nonconjugated diene copolymer (B1-2) described in detail below are preferred. The amorphous ethylene polymer (B1) is determined to be amorphous if its enthalpy of fusion is less than 10 J / g as observed by differential scanning calorimetry in a temperature range of 70°C to 140°C.
[0117] amorphous state Ethylene-α-olefin copolymer (B1-1)
[0118] The preferred amorphous ethylene-α-olefin copolymer (B1-1) used as the ethylene copolymer rubber (B) is an amorphous ethylene copolymer containing structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms. Preferably, in the amorphous ethylene-α-olefin copolymer (B1-1), the content of structural units derived from ethylene is greater than or equal to 50% by mass and less than 95% by mass, and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is greater than 5% by mass and less than or equal to 50% by mass (wherein, the total amount of the amorphous ethylene-α-olefin copolymer (B1-1) is set to 100% by mass), and the Mooney viscosity (ML) is... 1+4 The content of the substance is between 15 and 40 at 125℃, and the density is 0.850 g / cm³. 3Above and 0.890 g / cm 3 The following describes the amorphous ethylene-α-olefin copolymer (B1-1), which may have two or more structural units derived from α-olefins having four or more carbon atoms.
[0119] As for the α-olefin with 4 or more carbon atoms in the amorphous ethylene-α-olefin copolymer (B1-1), it is preferred to have 4 or more but less than 8 carbon atoms, such as 1-butene, 2-methylpropene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. As for the α-olefin with 4 or more but less than 8 carbon atoms, 1-butene, 1-hexene, or 1-octene are preferred.
[0120] In the amorphous ethylene-α-olefin copolymer (B1-1), the content of structural units derived from ethylene is preferably 50% by mass or more and 90% by mass or less, more preferably 52% by mass or more and 65% by mass or less, and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is preferably 10% by mass or more and 50% by mass or less, more preferably 35% by mass or more and 48% by mass or less (wherein, the total amount of the amorphous ethylene-α-olefin copolymer (B1-1) is set to 100% by mass).
[0121] The content of ethylene-derived structural units and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins with 4 or more carbon atoms in the amorphous ethylene-α-olefin copolymer (B1-1) can be determined by nuclear magnetic resonance spectroscopy (NMR).
[0122] As a method for manufacturing amorphous ethylene-α-olefin copolymer (B1-1), known polymerization methods using known catalysts for olefin polymerization can be listed, such as slurry polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization using complex catalysts such as Ziegler-Natta type catalysts, metallocene complexes, or non-metallocene complexes.
[0123] Ethylene-α-olefin-nonconjugated diene copolymer (B1-2)
[0124] The preferred ethylene-α-olefin-nonconjugated diene copolymer (B1-2) used as the ethylene copolymer rubber (B) is a nonconjugated diene copolymer having structural units derived from ethylene, structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms, and structural units derived from nonconjugated dienes, and is a copolymer in which the content of structural units derived from ethylene is 50% by mass or more. In the ethylene-α-olefin-nonconjugated diene copolymer (B1-2), the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is 25% by mass or more and 50% by mass or less (wherein, the total content of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is set as 100% by mass), the iodine value is 0.1 or more and 20 or less, and the Mooney viscosity (ML) is... 1+4 The molecular weight distribution (Mw / Mn) is preferably 40 or higher and 85 or lower at 125°C, and the molecular weight distribution (Mw / Mn) is preferably 1.5 or higher and 3.5 or lower.
[0125] As a method for manufacturing ethylene-α-olefin-nonconjugated diene copolymer (B1-2), known polymerization methods using known catalysts for olefin polymerization can be listed, such as slurry polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization using complex catalysts such as Ziegler-Natta type catalysts, metallocene complexes, or non-metallocene complexes.
[0126] To adjust the molecular weight of the generated ethylene-α-olefin-nonconjugated diene copolymer (B1-2), molecular weight regulators such as hydrogen can be used.
[0127] As the α-olefin with 4 or more carbon atoms in the ethylene-α-olefin-nonconjugated diene copolymer (B1-2), it is preferred to be an α-olefin with 4 or more but less than 8 carbon atoms, such as 1-butene, 2-methylpropene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. 1-Butene, 1-hexene, or 1-octene are preferred as α-olefins with 4 or more but less than 8 carbon atoms. α-olefins with 4 or more carbon atoms can be used alone or in combination of two or more.
[0128] Examples of non-conjugated dienes that provide structural units derived from non-conjugated dienes include: 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, and other chain-like non-conjugated dienes; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethimide-2-norbornene, 5-methylene-2-norbornene, 5-isocyanate, etc. Cyclic non-conjugated dienes such as propionyl-2-norbornene and 6-chloromethyl-5-isopropenyl-2-norbornene; trienes such as 2,3-diisopropionyl-5-norbornene, 2-idene-3-isopropionyl-5-norbornene, 2-propenyl-2,2-norbornene, 1,3,7-octtriene, and 1,4,9-decanetriene, preferably 5-ethide-2-norbornene, 5-vinylnorbornene, or dicyclopentadiene.
[0129] The content of ethylene-derived structural units in the ethylene-α-olefin-nonconjugated diene copolymer (B1-2) is preferably 50% by mass or more and 75% by mass or less, and more preferably 50% by mass or more and 65% by mass or less from the viewpoint of low-temperature impact resistance of the molded article. The content of structural units in component (B1-2) derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is preferably 25% by mass or more and 50% by mass or less, and more preferably 35% by mass or more and 50% by mass or less from the viewpoint of low-temperature impact resistance of the molded article (wherein, the total content of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is set to 100% by mass).
[0130] It should be noted that the content of ethylene-derived structural units and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins with 4 or more carbon atoms in the ethylene-α-olefin-nonconjugated diene copolymer (B1-2) can be determined by nuclear magnetic resonance spectroscopy (NMR).
[0131] The Mooney viscosity (ML) of the ethylene-α-olefin-nonconjugated diene copolymer (B1-2) measured at 125 °C. 1+4 The viscosity (at 125°C) is preferably 40 or higher and 85 or lower, more preferably 43 or higher and 75 or lower, and particularly preferably 45 or higher and 70 or lower. Mooney viscosity was measured according to BSTM D-1646.
[0132] The iodine value of the ethylene-α-olefin-nonconjugated diene copolymer (B1-2) is preferably 0.1 or higher and 20 or lower, more preferably 0.1 or higher and 15 or lower from the viewpoint of the rigidity of the molded article, and particularly preferably 0.1 or higher and 10 or lower. The iodine value refers to the number of grams of iodine used in the reaction of 100g of sample with iodine.
[0133] The iodine value of non-conjugated diene copolymers can be determined by infrared spectroscopy.
[0134] The molecular weight distribution of the ethylene-α-olefin-nonconjugated diene copolymer (B1-2) is preferably 1.5 or more and 3.5 or less. From the viewpoint of the low-temperature impact resistance of the molded article, it is more preferably 1.5 or more and 3.0 or less, and particularly preferably 1.5 or more and 2.3 or less.
[0135] Here, molecular weight distribution refers to the ratio of mass-average molecular weight (Mw) to number-average molecular weight (Mn) as determined by gel permeation chromatography, i.e., Mw / Mn.
[0136] Composition (B2): Crystalline ethylene derived from structural units of ethylene, comprising ≥50% and <90% by mass. olefin copolymers
[0137] The preferred component (B2) used as all or part of the ethylene copolymer rubber (B) is a crystalline ethylene copolymer with structural units derived from ethylene of greater than or equal to 50% by mass and less than 90% by mass.
[0138] Component (B2) is an olefin block copolymer containing ethylene polymer blocks and ethylene-α-olefin copolymer blocks. Component (B2) exhibits a crystallization melting peak in the temperature range of 70℃ to 140℃, with a melting enthalpy ΔH. m2 Preferably, it is 10 J / g to 70 J / g, more preferably 30 J / g to 50 J / g.
[0139] Enthalpy of fusion ΔH of component (B2) m2 It can be determined by analyzing a portion of the melting curve within a specified temperature range determined by differential scanning calorimetry according to the method of JIS K7122-1987. More specifically, it can be determined, for example, by the method described in the embodiments of this application.
[0140] Enthalpy of melting ΔH m2 The amount of ethylene polymer blocks can be adjusted appropriately. Generally, when the amount of ethylene polymer blocks decreases, the melting enthalpy ΔH is reduced. m2 The tendency to decrease.
[0141] As an ethylene polymer block in a crystalline ethylene copolymer (B2), it is based on ethylene units and may have structural units derived from other monomers in addition to those derived from ethylene. Examples of structural units derived from other monomers include those derived from 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. Preferably, it is a structural unit derived from α-olefins such as 1-propylene, 1-butene, 1-hexene, and 1-octene, where the terminal carbon atom has a carbon-carbon double bond and the number of carbon atoms is 3 to 8. It may be an ethylene polymer block obtained by copolymerizing only one of the α-olefins in component (B2) with ethylene, or it may be an ethylene polymer block obtained by copolymerizing two or more of the α-olefins in component (B2) with ethylene.
[0142] Examples of ethylene-α-olefin copolymer blocks in crystalline ethylene copolymers (B2) include those having structural units such as 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene, in addition to ethylene units. Preferably, the structural units are α-olefins with 4 to 8 carbon atoms, derived from 1-propylene, 1-butene, 1-hexene, or 1-octene, where the terminal carbon atoms have carbon-carbon double bonds. The ethylene-α-olefin copolymer block can be obtained by copolymerizing only one type of α-olefin in component (B2) with ethylene, or it can be obtained by copolymerizing two or more types of α-olefins in component (B2) with ethylene. Furthermore, crystalline ethylene copolymers (B2) can use only one type or a combination of two or more types.
[0143] The content of ethylene units in the crystalline ethylene copolymer (B2) is greater than or equal to 50% by mass and less than 90% by mass, preferably more than 50% by mass and less than 80% by mass, relative to the combined content of ethylene units and α-olefin units. For high-temperature impact resistance of the crystalline ethylene copolymer (B2), a higher content of ethylene units in component (B2) is preferred; from the viewpoint of low-temperature impact resistance, a lower content of ethylene units in component (B2) is preferred. The content of ethylene units in the crystalline ethylene copolymer (B2) is more preferably 70% by mass or less. It should be noted that the content of structural units derived from ethylene and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the crystalline ethylene copolymer (B2) can be determined by nuclear magnetic resonance spectroscopy (NMR).
[0144] In addition to ethylene units and α-olefin units with 3 to 8 carbon atoms, ethylene-α-olefin copolymers (B2) can also have other structural units, such as non-conjugated diene units. Examples of such non-conjugated dienes include: chain-like non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; and cyclic non-conjugated dienes such as cyclohexadiene, dimercyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethide-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, and 6-chloromethyl-5-isopropenyl-2-norbornene. Preferably, 5-ethide-2-norbornene and dimercyclopentadiene are used.
[0145] Furthermore, when the crystalline ethylene copolymer (B2) has other structural units such as non-conjugated diene units, the content of these other structural units, relative to the crystalline ethylene copolymer (B2) as a whole, is typically 10% by mass or less, preferably 5% by mass or less. The content of non-conjugated diene units and propylene units can be determined by infrared spectroscopy.
[0146] Specifically, the crystalline ethylene copolymer (B2) used in this embodiment can be exemplified as a block copolymer comprising crystalline ethylene polymer blocks and ethylene-α-olefin copolymer blocks such as ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-propylene-1-butene copolymer, ethylene-propylene-1-hexene copolymer, and ethylene-propylene-1-octene copolymer. One or more of these substances can be used. Among these, the crystalline ethylene copolymer (B2) is most preferably a block copolymer comprising ethylene polymer blocks and ethylene-1-octene copolymer blocks; that is, the crystalline ethylene copolymer (B2) is most preferably an olefin block copolymer comprising polymer blocks containing ethylene and ethylene-1-octene copolymer blocks.
[0147] The crystalline ethylene copolymer (B2) possesses not only crystalline ethylene-containing polymer blocks but also amorphous properties due to ethylene-α-olefin copolymer blocks. This amorphous property is manifested by the glass transition temperature. The glass transition temperature of the crystalline ethylene copolymer (B2), as determined by DSC, is preferably -80°C or higher, more preferably -75°C or higher, and more preferably -50°C or lower, more preferably -60°C or lower.
[0148] There is no limitation on the melt flow rate (measured at 190°C and under a load of 21.18 N) of the crystalline ethylene copolymer (B2), which is typically 10 g / 10 min or less, preferably 8 g / 10 min or less from the viewpoint of strength, more preferably 5 g / 10 min or less, and even more preferably 3 g / 10 min or less. Furthermore, the melt flow rate of the crystalline ethylene copolymer (B2) is typically 0.01 g / 10 min or more, preferably 0.05 g / 10 min or more from the viewpoint of flowability, and even more preferably 0.10 g / 10 min or more. The melt flow rate of component (B) was measured according to BSTM D1238 at a measurement temperature of 190°C and a measurement load of 21.18 N.
[0149] From the perspective of low-temperature impact resistance, the preferred density of the crystalline ethylene copolymer (B2) is 0.880 g / cm³. 3 The preferred value is 0.870 g / cm³. 3 Below. On the other hand, there is no particular limitation on the lower limit of the density of crystalline ethylene copolymers (B2), which is typically 0.850 g / cm³. 3 above.
[0150] As a method for manufacturing crystalline ethylene copolymers (B2), it can be synthesized according to the methods disclosed in Japanese Patent Application Publication Nos. 2007-529617, 2008-537563, and 2008-543978. For example, it can be manufactured by a process in which a composition comprising a mixture or reaction product obtained by combining a first olefin polymerization catalyst, a second olefin polymerization catalyst, and a chain shuttle is prepared, and the ethylene and α-olefin are contacted with the composition under addition polymerization conditions, wherein the second olefin polymerization catalyst is capable of preparing a polymer with chemical or physical properties different from those of a polymer prepared using the first olefin polymerization catalyst under the same polymerization conditions.
[0151] Continuous solution polymerization is preferred for the polymerization of crystalline ethylene copolymers (B2). In continuous solution polymerization, catalyst components, chain shuttles, monomers, and, depending on the situation, solvents, auxiliaries, scavengers, and polymerization aids are continuously supplied to the reaction zone, and polymer products are continuously removed from the reaction zone. Furthermore, the block length can be varied by controlling the ratio and type of the catalyst, the ratio and type of the chain shuttle, the polymerization temperature, etc.
[0152] It should be noted that the other conditions in the synthesis method of block copolymers are disclosed in Japanese Patent Application Publication Nos. 2007-529617, 2008-537563, and 2008-543978. Furthermore, commercially available products include, for example, the Engage (registered trademark)-XLT series and INFUSE (registered trademark) series manufactured by Dow Chemical Company.
[0153] Organic peroxides
[0154] The method for manufacturing the thermoplastic elastomer composition of the present invention uses an organic peroxide in its first step. It should be noted that, due to the decomposition of the organic peroxide, it may sometimes be absent from the manufactured thermoplastic elastomer composition. Furthermore, as described later, it is preferable that the organic peroxide is substantially absent in the second step.
[0155] Organic peroxides act as crosslinking agents, primarily through melt mixing in the first step, to crosslink the ethylene copolymer rubber (B) and break the molecular chains of polypropylene (A-1), thereby obtaining a thermoplastic elastomer composition or its precursor that has both rubber elasticity and thermoplasticity.
[0156] Examples of organic peroxides include: peroxide ketones, peroxide diacyls, hydroperoxides, peroxide dialkyls, peroxide ketals, alkyl peresters, percarbonates, peroxide dicarbonates, and peroxide esters.
[0157] Preferred examples of specific organic peroxides include: dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 1,3-bis(tert-butylperoxyisopropyl)benzene, tert-butylcumyl peroxide, di-tert-butyl peroxide, 2,2,4-trimethylpentyl-2-hydroperoxide, diisopropylbenzene hydroperoxide, isopropylbenzene peroxide, tert-butyl peroxide, 1,1-di(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, isobutyl peroxide, 2,4-dichlorobenzoyl peroxide, o-methylbenzoyl peroxide, di(3,5,5-trimethylhexanoyl peroxide), lauroyl peroxide, benzoyl peroxide, and p-chlorobenzoyl peroxide; and combinations of two or more of these.
[0158] There are no particular restrictions on the amount of organic peroxide used. It is sufficient to set an amount that can achieve sufficient crosslinking of the ethylene copolymer rubber (B) and inhibit the excessive decomposition of polypropylene (A-1) and (A-2) in the first process.
[0159] For example, regarding the amount of organic peroxide used, when the total amount of polypropylene (A-1) and ethylene copolymer rubber (B) is set to 100 parts by mass, it is preferable to use 0.01 to 0.3 parts by mass of organic peroxide, and particularly preferable to use 0.05 to 0.28 parts by mass of organic peroxide.
[0160] The crosslinking agent can be supplied directly to the first process or in the form of being dissolved or dispersed in mineral oil.
[0161] Crosslinking aids
[0162] In the method for manufacturing the thermoplastic elastomer composition of the present invention, it is preferable to use the crosslinking aid together with the aforementioned organic peroxide. By using the crosslinking aid, crosslinking in the first step proceeds rapidly and uniformly, thus enabling the manufacture of a higher quality thermoplastic elastomer composition.
[0163] Examples of crosslinking aids include peroxide crosslinking aids such as N,N'-m-phenylenebismaleimide, toluene-2-bismaleimide, p-benzoquinone dioxime, nitrosobenzene, diphenylguanidine, and trimethylolpropane; or polyfunctional vinyl monomers such as divinylbenzene, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and allyl methacrylate.
[0164] Mineral oil (C)
[0165] In the method for manufacturing the thermoplastic elastomer composition of the present invention, mineral oil (C) can be used as long as the content of mineral oil (C) in the manufactured thermoplastic elastomer composition is 5% by mass or less.
[0166] By having a mineral oil (C) content of 5% by mass or less, the seepage of mineral oil (C) and the like from the above-mentioned thermoplastic elastomer composition can be effectively suppressed. Therefore, the above-mentioned thermoplastic elastomer composition can be appropriately used in automotive interior trim materials such as airbag covers used in high-temperature environments.
[0167] On the other hand, by using mineral oil (C), especially by using mineral oil (C) to oil-extrude ethylene copolymer rubber (B), it becomes easier to mix and melt-blend the starting materials, and it becomes easier to improve uniformity and control the microstructure of the composition.
[0168] When the total amount of the above thermoplastic elastomer composition is set to 100% by mass, the amount of mineral oil (C) used is preferably 0.1% to 5.0% by mass, more preferably 0.5% to 4.0% by mass.
[0169] Preferred examples of mineral oil (C) include paraffinic mineral oil, naphthenic mineral oil, and aromatic mineral oil, with paraffinic mineral oil being particularly preferred. Mineral oil (C) can be added during the melt blending of polypropylene (A-1) and ethylene copolymer rubber (B), or either component can be pre-mixed with mineral oil (C) before the melt blending. Examples of methods for mixing ethylene copolymer rubber (B) and mineral oil (C) include: (1) mixing solid ethylene copolymer rubber (B) and mineral oil (C) using a mixer; and (2) mixing a solution of ethylene copolymer rubber (B) with mineral oil (C) to produce a mixture, followed by removing the solvent from the mixture.
[0170] It should be noted that, in this specification, the term "mineral oil" refers to a substance derived from petroleum hydrocarbons, comprising at least one compound selected from the group consisting of aromatic compounds, cycloalkane compounds, and paraffin compounds, and which is liquid or oily at room temperature.
[0171] Other ingredients
[0172] In the method for manufacturing the thermoplastic elastomer composition of the present invention, various additives may be added in addition to the above-mentioned components.
[0173] As an additive, it may contain, for example, polymers or oligomers other than polypropylene (A-1), polypropylene (A-2), ethylene copolymer rubber (B), and mineral oil (C) mentioned above; softeners other than mineral oil (C); inorganic fillers (talc, calcium carbonate, calcined kaolin, glass fiber, hollow glass spheres, silica, metal soap, titanium dioxide, mica, potassium titanate fiber, etc.); organic fillers (fiber, wood flour, cellulose powder, carbon fiber, carbon black, etc.); lubricants (silicone oil, pure silicone rubber, etc.); antioxidants (phenols, sulfur-containing compounds, phosphorus-containing compounds, lactones, vitamins, etc.); and weather stabilizers. Stabilizers, UV absorbers (benzotriazoles, triazines, aniline derivatives, benzophenones, etc.), heat stabilizers, light stabilizers (hindered amines, benzoate esters, etc.), pigments (inorganic pigments, organic pigments, pigment dispersants, etc.), nucleating agents, foaming agents, foaming nucleating agents, plasticizers, flame retardants, brightening agents, antibacterial agents, light diffusing agents, adsorbents (metal oxides (zinc oxide, magnesium oxide, etc.), wetting and dispersing agents, VOC / odor removers, water-retaining agents (including aqueous media containing amphiphilic polymers, etc.), abrasion resistance improvers, metal chlorides (ferric chloride, calcium chloride, etc.), hydrotalcite, aluminates, etc.). These additives can be used alone or in combination of two or more.
[0174] Resins other than the aforementioned polypropylene (A-1), polypropylene (A-2), ethylene copolymer rubber (B), and mineral oil (C) can include: olefin resins (excluding resins equivalent to the aforementioned polypropylene (A-1), polypropylene (A-2), ethylene copolymer rubber (B), or mineral oil (C),) olefin elastomers (excluding elastomers equivalent to the aforementioned polypropylene (A-1), polypropylene (A-2), ethylene copolymer rubber (B), or mineral oil (C), hydrogenated products of block copolymers containing polymer blocks of monovinyl substituted aromatic hydrocarbon compounds and polymer blocks of conjugated diene compounds, polyphenylene ether resins, polyamide resins, polyester resins, polyoxymethylene resins, polymethyl methacrylate resins, etc.
[0175] Examples of olefin resins include: functionalized ethylene polymers such as ethylene-vinyl acetate (“EVA”), polymers having maleic anhydride grafted onto polyolefins such as polypropylene, and ethylene-acrylate copolymers such as ethylene-methyl acrylate copolymers (“EMA”).
[0176] Manufacturing of thermoplastic elastomer compositions
[0177] First process
[0178] The first step in the method for manufacturing the thermoplastic elastomer composition of the present invention is to determine the intrinsic viscosity [η] of the xylene-insoluble component at 20°C in the presence of an organic peroxide. cxis The process of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) with a concentration of ≥0.1dl / g and ≤1.5dl / g.
[0179] In the first step, the product can be manufactured by compounding the aforementioned polypropylene (A-1), ethylene copolymer rubber (B), and other components such as mineral oil (C), various additives, and crosslinking aids in the presence of organic peroxides using conventional methods, such as a conventional extruder, Banbury mixer, rollers, Brabender plasticizer, or Brabender kneader. An extruder, particularly a twin-screw extruder, is preferred. Alternatively, all components to be compounded can be melt-mixed together, or a portion of the components can be compounded, and then the remaining components added and melt-mixed; one or more melt-mixing processes can be performed. The melt-mixing temperature in the first step is preferably 150°C to 300°C, more preferably 180°C to 250°C. The melt-mixing time is preferably 5 seconds to 30 minutes, more preferably 20 seconds to 20 minutes. The components can be added in any order or simultaneously.
[0180] By melt-blending in the presence of organic peroxides, preferably under the above conditions, rubber elasticity is exhibited by crosslinking the ethylene copolymer rubber (B), and fluidity (thermoplasticity) is maintained by cleaving the main chain of polypropylene (A-1). Therefore, a thermoplastic elastomer composition possessing both rubber elasticity and thermoplasticity can be obtained. It should be noted that since the resin composition obtained in the first step may have a different composition, physical properties, etc., than the desired thermoplastic elastomer composition, it is also referred to as a "precursor to a thermoplastic elastomer composition."
[0181] Second process
[0182] In the second step, the intrinsic viscosity [η] of the xylene-insoluble component at 20°C is further added to the thermoplastic elastomer composition precursor obtained in the first step. cxis The polypropylene (A-2) having a content of 1.5 dl / g or more and 7 dl / g or less was melt-blended. Further addition of polypropylene (A-2) further improved the rigidity of the resulting thermoplastic elastomer composition.
[0183] More specifically, for injection-molded articles made from thermoplastic elastomer compositions obtained by the manufacturing method of the present invention under the following conditions, according to JIS K7171, test pieces are placed symmetrically with respect to the two support tables at right angles to the indenter and support tables, the test speed is set to 1 mm / min, and the flexural modulus measured at a standard atmosphere of 23°C / 50%RH is preferably 330 MPa or more, more preferably 340 MPa or more, and particularly preferably 350 MPa or more.
[0184] Molding method: Injection molding
[0185] Barrel temperature: 220℃
[0186] Mold temperature: 50℃
[0187] Injection rate: 25cm 3 / Second
[0188] Molded body dimensions: Width 90mm × Length 150mm × Thickness 2.0mm
[0189] There are no particular restrictions on the conditions of the second step, and the second step can be carried out in the following manner: preferably, the intrinsic viscosity [η] of the thermoplastic elastomer composition precursor obtained in the first step and the xylene-insoluble component at 20°C is introduced into the same extruder as the first step, which is a twin-screw extruder, and more preferably, into the same extruder as the extruder used in the first step. cxis The polypropylene (A-2) is of 1.5 dl / g or higher and 7 dl / g or lower, and is then melt-blended.
[0190] The preferred temperature for the second melting and mixing process is 150°C to 300°C, more preferably 180°C to 250°C. There is no particular limitation on the heat treatment time, but it is preferably 5 seconds to 30 minutes, more preferably 10 seconds to 10 minutes.
[0191] The second step is preferably carried out under conditions where organic peroxides are substantially absent. In this case, since the crosslinking or decomposition of the resin components, particularly polypropylene (A-2), does not substantially occur in the second step, the resin composition, molecular weight distribution, gel fraction, etc., of the thermoplastic elastomer composition can be adjusted with a high degree of freedom. For example, since the decomposition of polypropylene (A-2), which is easily decomposed by organic peroxides, can be suppressed, it becomes easier to control rigidity and other properties by adding this polypropylene (A-2).
[0192] Since organic peroxides decompose through melt blending, from the viewpoint of performing the second process under conditions where organic peroxides are substantially absent, it is preferable to decompose substantially all organic peroxides through melt blending in the first process. Therefore, the temperature during melt blending in the first process is particularly preferably 190°C to 250°C. There is no particular limitation on the heat treatment time, but it is preferably 5 seconds to 30 minutes, and more preferably 10 seconds to 10 minutes.
[0193] From the viewpoint that substantially all organic peroxides are decomposed through the melt mixing in the first process, regarding the amount of organic peroxide used in the first process, when the total amount of polypropylene (A-1) and ethylene copolymer rubber (B) is set to 100 parts by mass, it is preferable to use 0.01 to 0.3 parts by mass of organic peroxide, and particularly preferable to use 0.05 to 0.28 parts by mass of organic peroxide.
[0194] From the viewpoint of cost and smooth transfer to the second process while maintaining the molten state, as described above, it is preferable to perform the first and second processes in the same extruder. In this case, it is preferable to provide multiple feed ports in the extruder, supplying polypropylene (A-1), ethylene copolymer rubber (B), and organic peroxide from the upstream first feed port to perform the first process, and supplying polypropylene (A-2) from a more downstream feed port and mixing it with the thermoplastic elastomer composition precursor obtained in the first process to perform the second process.
[0195] In the method for manufacturing the thermoplastic elastomer composition of the present invention, there is no particular limitation on the amount of each component used. From the viewpoint of properly controlling the physical properties of the thermoplastic elastomer composition, in the second step, relative to a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B) (since the mass of mineral oil is not included in the calculation, the mass of mineral oil is subtracted when ethylene copolymer rubber (B) is oiled with mineral oil), it is preferable to supply 0.1 to 15 parts by mass of polypropylene (A-2), and more preferably 1.0 to 10 parts by mass of polypropylene (A-2).
[0196] Furthermore, from the viewpoint of manufacturing a thermoplastic elastomer composition precursor with a suitable structure in the first process, based on a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B), it is preferable to use 30 to 70 parts by mass of polypropylene (A-1) and 70 to 30 parts by mass of ethylene copolymer rubber (B), and particularly preferable to use 40 to 60 parts by mass of polypropylene (A-1) and 60 to 40 parts by mass of ethylene copolymer rubber (B).
[0197] The thermoplastic elastomer composition manufactured by the manufacturing method of the present invention can be used for a variety of purposes, and there are no particular limitations on its use. However, since the orientation of cross-linked rubber particles can be suppressed even in narrow parts such as molds during injection molding, adverse effects on appearance can be effectively prevented. Therefore, it is particularly preferred for the manufacture of injection molded articles, especially injection molded articles used in an uncoated manner.
[0198] Furthermore, the thermoplastic elastomer composition of this embodiment can produce molded articles that possess both excellent appearance and rigidity at a high level, making it suitable for applications requiring these properties. For example, it can be used in automotive parts, industrial machinery parts, electronic and electrical equipment parts, building materials, etc., but is not limited thereto.
[0199] Of the aforementioned applications, it is particularly suitable for use in automotive interior parts with a wide operating temperature range, especially for airbag housings. In airbag housing applications, a high level of excellent appearance and rigidity is required, but there are many narrow sections in the mold during molding, and it is often used unpainted. Since passenger-side airbag housings are generally large, even higher rigidity is required, making it particularly suitable as the thermoplastic elastomer composition of this embodiment.
[0200] In this embodiment, the thermoplastic elastomer composition of this embodiment can be used to mold the airbag housing using, for example, conventional injection molding or, as needed, various molding methods such as gas injection molding, injection compression molding, and short-shot foaming. Examples of molding conditions in the above-described injection molding include: a molding temperature typically 100°C to 300°C, preferably 150°C to 280°C; an injection pressure of 5 MPa to 100 MPa, preferably 10 MPa to 80 MPa; and a mold temperature of 20°C to 80°C, preferably 20°C to 60°C.
[0201] [Example]
[0202] The physical properties in the examples / comparative examples were evaluated using the following methods.
[0203] [Determination of physical properties]
[0204] 1. Melt Flow Rate (MFR)
[0205] The melt flow rate was determined by method B according to JIS K7210 at 190℃ or 230℃ and a load of 21.18N.
[0206] 2. Enthalpy of fusion ΔH m2
[0207] Enthalpy of fusion ΔH in the temperature range above 70℃ and below 140℃ m2 The heat of fusion is determined by analyzing the portion of the melting curve measured by the differential scanning calorimetry method below, which is above 70°C and below 140°C, according to JIS K7122-1987.
[0208] The crystallization melting peak temperature in the temperature range of 70°C to 140°C is determined by analyzing the portion of the melting curve in the temperature range of 70°C to 140°C obtained by differential scanning calorimetry as described below, according to JIS K7121-1987.
[0209] The glass transition temperature is determined as the intermediate glass transition temperature obtained by analyzing the melting curve determined by the differential scanning calorimetry method described below, in accordance with JIS K7121-1987.
[0210] In the differential scanning calorimetry curves during the heating operation measured using a differential scanning calorimeter, the peak temperature of the endothermic peak with the largest peak temperature is taken as the melting temperature.
[0211] <Measurement Conditions>
[0212] Cooling procedure: Melt the sample at 220°C, then cool it from 220°C to -80°C at a cooling rate of 10°C / min.
[0213] Heating operation: After cooling from 220℃ to -80℃, immediately heat up from -80℃ to 220℃ at a rate of 10℃ / minute.
[0214] 3. Intrinsic viscosity of xylene-soluble components at 20℃ and xylene-insoluble components at 20℃ (η) cxs ]、[η cxis (Unit: dl / g)
[0215] Approximately 5g of sample was completely dissolved in 500ml of boiling xylene. The xylene solution was then slowly cooled to 20°C and allowed to settle at 20°C for at least 4 hours. The precipitate was then separated from the solution by filtration. The precipitate was designated as the CXIS fraction, and the substance obtained by removing the solvent from the solution was designated as the CXS fraction.
[0216] The specific viscosity was measured in tetrahydronaphthalene at 135°C using an Ubbelohde viscometer. The intrinsic viscosity was determined by extrapolation from the obtained specific viscosity using the calculation method described on page 491 of "Polymer Solutions, Polymer Experimentation 11" (published by Kyoritsu Publishing Co., Ltd. in 1982).
[0217] 4. Digits in five-unit groups according to the equivalence principle
[0218] The determination was carried out by nuclear magnetic resonance spectroscopy (NMR) under the following conditions (1) to (7). The ratio of the area of the NMR peaks belonging to mmmm to the area of the NMR peaks in the methyl carbon region was calculated according to the method described in the literature (Macromolecules, 6, 925 (1973)), thereby determining the isotactic five-unit group number.
[0219] (1) Equipment: Avance III HD600 manufactured by BRUKER
[0220] (10mm cryoprobe)
[0221] (2) Solvent for determination: 1,2-dichlorobenzene-d4 / 1,2-dichlorobenzene
[0222] (20 / 80 volume ratio)
[0223] (3) Measurement temperature: 130℃
[0224] (4) Measurement method: proton decoupling method
[0225] (5) Pulse width: 45 degrees
[0226] (6) Pulse repetition time: 4 seconds
[0227] (7) Chemical shift standard: tetramethylsilane
[0228] 5. The content of ethylene-derived structural units and structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the non-conjugated diene copolymer of component (B).
[0229] The non-conjugated diene copolymer was formed into a film with a thickness of approximately 0.1 mm using a hot press, and the infrared absorption spectrum of the film was measured using an infrared spectrophotometer (IR-810 manufactured by Nippon Spectroscopy Industry Co., Ltd.). Following the method described in the literature (Characterization of Polyethylene Using Infrared Absorption Spectroscopy), by Takayama, Usami et al.; or Die Makromolekulare Chemie, 177, 461 (1976) by Mc Rae, MA, Madam S, WF et al.), the content of ethylene-derived structural units and the content of structural units derived from at least one monomer selected from the group consisting of propylene and α-olefins with 4 or more carbon atoms in the non-conjugated diene copolymer were determined based on the infrared absorption spectrum.
[0230] 6. Iodine value of the non-conjugated diene copolymer of component (B)
[0231] The non-conjugated diene copolymer was molded into a film with a thickness of approximately 0.5 mm using a hot press. The peak (1611 cm⁻¹) generated by the dimercyclopentadiene in the film was determined using an infrared spectrophotometer. -1 The absorption peak of 5-ethylidene-2-norbornene and the peak produced by 5-ethylidene-2-norbornene (1688 cm⁻¹) -1 The intensity of the absorption peak (of the double bond) is used to determine the molar content of the double bond, and the iodine value is calculated from the molar content.
[0232] 7. Molecular weight distribution
[0233] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) were determined by gel permeation chromatography (GPC) under the following conditions (1) to (9), and the molecular weight distribution (Mw / Mn) was calculated.
[0234] (1) Device: HLC-8121GPC / HT manufactured by Tosoh Corporation
[0235] (2) Separation column: Three GMHHR-H(S)HT columns manufactured by Tosoh Corporation
[0236] (3) Measurement temperature: 140℃
[0237] (4) Carrier: o-dichlorobenzene
[0238] (5) Flow rate: 1.0 mL / min
[0239] (6) Sample concentration: approximately 1 mg / mL
[0240] (7) Injection volume: 400 μL
[0241] (8) Detector: Differential refractive index detector
[0242] (9) Molecular weight standard material: Standard polystyrene
[0243] 8. Mooney viscosity
[0244] Mooney viscosity was determined at 125°C according to ASTM D-1646.
[0245] 9. Density (unit: g / cm³) 3 )
[0246] Density was determined according to JIS K7112 without annealing.
[0247] 10. Content of ethylene-derived structural units in the ethylene copolymers of components (A) and (B) (unit: mass%)
[0248] The determination was carried out by nuclear magnetic resonance spectroscopy (NMR) under the following conditions (1) to (7), and the content of ethylene-derived structural units in the ethylene copolymer was determined according to the method described in the literature (JMS-REV.MACROMOL.CHEM.PHYS.,C29,201-317(1989)). The total amount of the ethylene copolymer was set to 100% by mass.
[0249] (1) Equipment: Avance III HD600 manufactured by BRUKER
[0250] (10mm cryoprobe)
[0251] (2) Solvent for determination: 1,1,2,2-tetrachloroethane-d2 / 1,2-dichlorobenzene (15 / 85 volume ratio)
[0252] (3) Measurement temperature: 135℃
[0253] (4) Measurement method: proton decoupling method
[0254] (5) Pulse width: 45 degrees
[0255] (6) Pulse repetition time: 4 seconds
[0256] (7) Chemical shift standard: tetramethylsilane
[0257] 11. Manufacturing method of injection molded articles
[0258] Using an EC160NII injection molding machine manufactured by Toshiba Machine Co., Ltd., with a side-gate flat mold, the injection was performed at a barrel temperature of 220°C, a mold temperature of 50°C, and an injection speed of 25cm. 3 Under the condition of / second, the thermoplastic elastomer compositions of the examples and comparative examples were injection molded to obtain injection molded articles with a longitudinal length of 90 mm, a transverse length of 150 mm, and a thickness of 2.0 mm.
[0259] 12. Stiffness (bending modulus)
[0260] The flexural modulus of the injection-molded article manufactured in section 11 above shall be determined according to JIS K7171. It should be noted that the test atmosphere shall be determined according to JIS K7100 at a standard atmosphere of 23°C / 50%RH.
[0261] 13. Low-temperature impact resistance (IZOD impact strength)
[0262] The impact resistance of the injection-molded articles manufactured in section 11 above was determined according to JIS K7110. It should be noted that the test was conducted at -45°C.
[0263] The measurement results are judged in the following manner.
[0264] P (Partial Fracture): Incomplete fracture that does not meet the definition of hinge fracture.
[0265] H (Hinge Fracture): Incomplete fracture of the test piece where the thin, hinge-like surface layer, having lost only bending stiffness, remains as a single unit without separation.
[0266] C (Complete Fracture): The test piece breaks into two or more fragments.
[0267] 14. Appearance
[0268] [Injection-molded parts for appearance evaluation]
[0269] Using an injection molding machine (trade name EC160NII100-EN manufactured by Toshiba Machine Co., Ltd.), the thermoplastic elastomer compositions of the examples and comparative examples were molded into box-shaped molded bodies with a tear line portion having a thickness of 0.5 mm (see reference). Figure 1 The uneven gloss of the surface of the torn line area of the molded body is visually observed and judged according to the following criteria.
[0270] ◎…Completely free of uneven shine
[0271] ○…The unevenness of the gloss is not obvious or almost non-existent.
[0272] ×… Clear unevenness of gloss can be observed.
[0273] [raw material]
[0274] Details of the starting materials used in the examples / comparative examples are described below.
[0275] <Polypropylene (A)>
[0276] (A-1-i)propylene homopolymer (h-PP)
[0277] MFR (230℃) = 40g / 10 minutes, [η cxis = 1.25 dl / g
[0278] (A-1-ii) A multiphase propylene polymer material comprising propylene homopolymer (I) and ethylene-propylene copolymer (II) manufactured by multi-step polymerization (NOBLEN WPX5343 manufactured by Sumitomo Chemical Co., Ltd.)
[0279] (MFR = 60g / 10min; Melting temperature = 163.5℃; [η] cxs ] = 5.3 dl / g; [η cxs ] / [η cxis =4.5; (Isometric five-unit group score = 0.98)
[0280] The content of propylene homopolymer (I) is 87% by mass;
[0281] Content of ethylene-propylene copolymer (II) = 13% by mass
[0282] The content of ethylene-derived monomer units in the ethylene-propylene copolymer (II) is 32% by mass.
[0283] The content of propylene-derived monomer units in the ethylene-propylene copolymer (II) is 68% by mass.
[0284] (A-1-iii) A multiphase propylene polymer material comprising propylene homopolymer (I) and ethylene-propylene copolymer (II) manufactured by multi-step polymerization (NOBLEN AZ564 manufactured by Sumitomo Chemical Co., Ltd.)
[0285] (MFR = 28.5 g / 10 minutes; melting temperature = 164.6 °C; [η] cxs ] = 2.4 dl / g; [η cxs ] / [η cxis =2.1; the fraction of the five units of the isoclinic = 0.98)
[0286] The content of propylene homopolymer (I) is 87% by mass;
[0287] Content of ethylene-propylene copolymer (II) = 13% by mass
[0288] The content of ethylene-derived monomer units in the ethylene-propylene copolymer (II) is 46% by mass.
[0289] The content of propylene-derived monomer units in the ethylene-propylene copolymer (II) is 52% by mass.
[0290] (A-1-iv) Ethylene-propylene copolymer
[0291] NOBLEN Z144CE4 manufactured by Sumitomo Chemical Co., Ltd.
[0292] (MFR = 27g / 10 minutes; [η] cxis =1.4 dl / g; melting temperature = 141℃)
[0293] The content of monomer units derived from propylene is 96% by mass;
[0294] The content of monomer units derived from ethylene = 4% by mass
[0295] (A-2-i) propylene homopolymer (h-PP)
[0296] MFR (230℃) = 0.5g / 10 minutes, [η cxis = 3.0 dl / g
[0297] (A-2-ii) Propylene homopolymer (h-PP)
[0298] (A-2-ii) is a propylene homopolymer produced by multi-step polymerization. (A-2-ii) is a mixture of propylene homopolymer component b1 produced in the previous step and propylene homopolymer component b2 produced in the next step. The content of propylene homopolymer component b1 in the previous step is 18% by mass, and the content of propylene homopolymer component b2 in the next step is 82% by mass.
[0299] MFR (230℃) = 11g / 10min, melting temperature = 165℃, (A-2-ii) overall [η cxis ] total =2.0 dl / g, b1 of [η] cxis ] = 7.0 dl / g, b2 of [η cxis = 0.92 dl / g
[0300] <Ethylene copolymer rubber (B)>
[0301] (B1-1-i)Ethylene-1-octene copolymer
[0302] Engage 8842 manufactured by Dow Chemical Company
[0303] The enthalpy of fusion ΔH observed by differential scanning calorimetry in the temperature range above 70℃ and below 140℃ m2 =0 J / g, content of structural units derived from ethylene = 55% by mass, content of structural units derived from 1-octene = 45% by mass, Mooney viscosity (ML) 1+4 (125℃) = 23, density = 0.857 g / cm³ 3
[0304] (B1-1-ii) Ethylene-1-butene copolymer
[0305] Engage 7487 manufactured by Dow Chemical Company
[0306] The content of monomer units derived from ethylene was 69.1% by mass, the content of monomer units derived from 1-butene was 30.9% by mass, the iodine value was 0, the molecular weight distribution was 1.9, and the proportion of eluent at an elution temperature of -15°C, as determined by CFC analysis, was 24.3% by mass of the total eluent.
[0307] (B1-2-i) Ethylene-propylene-5-ethylidene-2-norbornene copolymer
[0308] Preparation method
[0309] Hexane, ethylene, and propylene are supplied to a first stainless steel polymerization tank equipped with a stirrer at a rate of 408 g / (h·L) per unit time and per unit volume of polymerization tank, respectively. VOCl3 is mixed and stirred at a rate of 26.5 mg / (h·L) and ethanol at a rate of 12.7 mg / (h·L) (VOCl3 / ethanol = 1 / 1.8 molar ratio) in a pipeline mixer, and then fed into the polymerization tank. Ethyl sesquichloride (EASC) is supplied to the polymerization tank at a rate of 158.7 mg / (h·L) and hydrogen at a rate of 0.05 NL / (h·L). 5-Ethylidene-2-norbornene is further supplied to the polymerization tank at a rate of 0.5 g / (h·L). The temperature of the polymerization tank is maintained at 41°C. In the polymerization tank, 38 g / (h·L) of non-conjugated diene copolymer was produced per unit time and per unit volume of polymerization tank. Next, the polymerization solution drawn from the first polymerization tank was supplied to a second stainless steel polymerization tank of the same volume as the first polymerization tank, equipped with a stirrer. Hexane was supplied at a rate of 204 g / (h·L), ethylene at a rate of 15.2 g / (h·L), and propylene at a rate of 100.4 g / (h·L), per unit volume of polymerization tank. VOCl3 was mixed and stirred in a pipeline mixer at a rate of 16.7 mg / (h·L) and ethanol at a rate of 8.0 mg / (h·L) (VOCl3 / ethanol = 1 / 1.8 molar ratio), and then supplied to the polymerization tank. Additionally, ethyl aluminum sesquichloride (EASC) was supplied to the polymerization tank at a rate of 66.8 mg / (h·L). The temperature of the polymerization tank was maintained at 45°C. In the second polymerization tank, 19 g / (hour·L) of non-conjugated diene copolymer was generated per unit time and per unit polymerization tank volume.
[0310] The Mooney viscosity (ML) of the non-conjugated diene copolymer obtained by the above preparation method is... 1+4 The content of structural units derived from ethylene (at 125℃), the content of structural units derived from propylene, the iodine value, and the molecular weight distribution are as follows.
[0311] Mooney viscosity (ML) 1+4 =65 (125℃), MFR (190℃, 21.18N) = 0.5 g / 10 min, content of structural units derived from ethylene = 55% by mass, content of structural units derived from propylene = 45% by mass, iodine value = 2.1, molecular weight distribution = 1.9, enthalpy of fusion ΔH observed by differential scanning calorimetry in the temperature range above 70℃ and below 140℃. m2 =0 J / g.
[0312] (B1-2-ii) Ethylene-propylene-5-ethylidene-2-norbornene copolymer
[0313] Preparation method
[0314] Hexane was supplied to a first stainless steel polymerization tank equipped with a stirrer at a rate of 705 g / (h·L) per unit time and per unit volume of polymerization tank, ethylene at a rate of 36.4 g / (h·L) and propylene at a rate of 89.2 g / (h·L). VOCl3 was mixed and stirred in a pipeline mixer at a rate of 30.4 mg / (h·L) and then fed into the polymerization tank. Ethyl sesquichloride (EASC) was supplied to the polymerization tank at a rate of 182.7 mg / (h·L) and hydrogen at a rate of 0.08 NL / (h·L). 5-Ethylidene-2-norbornene was further supplied to the polymerization tank at a rate of 0.5 g / (h·L). The temperature of the polymerization tank was maintained at 45°C. In this polymerization tank, 44 g / (h·L) of a non-conjugated diene copolymer was produced per unit time and per unit volume of polymerization tank.
[0315] Next, the polymerization solution drawn from the first polymerization tank was supplied to a second stainless steel polymerization tank of the same volume as the first polymerization tank, equipped with a stirrer. Hexane was supplied at a rate of 259 g / (h·L) per unit time and per unit polymerization tank volume, ethylene at a rate of 21.4 g / (h·L) and propylene at a rate of 75.0 g / (h·L). VOCl3 was mixed and stirred in a pipeline mixer at a rate of 30.9 mg / (h·L) and then supplied to the polymerization tank. Additionally, ethyl sesquichloride (EASC) was supplied to the polymerization tank at a rate of 92.8 mg / (h·L). The temperature of the polymerization tank was maintained at 56°C. In the second polymerization tank, 22 g / (h·L) of a non-conjugated diene copolymer was generated per unit time and per unit polymerization tank volume.
[0316] The Mooney viscosity (ML) of the non-conjugated diene copolymer obtained by the above preparation method is... 1+4 The contents of monomer units derived from ethylene (125℃), monomer units derived from propylene, iodine value, molecular weight distribution, and the proportion of eluents at an elution temperature of -15℃ as determined by CFC are described below.
[0317] Mooney viscosity (ML) 1+4,125℃)=46, content of monomer units derived from ethylene=67% by mass, content of monomer units derived from propylene=33% by mass, iodine value=3, molecular weight distribution=2.2, proportion of eluent at elution temperature of -15℃ determined by CFC=41.8% by mass of total elution.
[0318] (B2-1) Olefin Block Copolymer (OBC)
[0319] The product manufactured by Dow Chemical Company is marketed under the brand name "Engage XLT8677".
[0320] The melting peak temperature is 118℃, and the enthalpy of fusion ΔH observed by differential scanning calorimetry in the temperature range above 70℃ and below 140℃ is [value missing]. m2 =42 J / g, MFR (190℃, 21.18 N) = 0.5 g / 10 min, glass transition temperature (DSC method) = -67℃, density = 0.870 g / cm³ 3 The content of structural units derived from ethylene is 52% by mass, and the content of structural units derived from 1-octene is 48% by mass.
[0321] (C-1) Paraffinic mineral oil (trade name Diana Process Oil PW-380 manufactured by Idemitsu Kosan Co., Ltd.)
[0322] • APO10-DL: A reagent containing 10% by mass of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (crosslinking agent) and 90% by mass of paraffinic oil (APO10-DL manufactured by Akzo Chemical Co., Ltd.)
[0323] • HiCross MS50: A reagent containing 50% by mass of trimethylolpropane trimethacrylate (crosslinking aid) and 50% by mass of silica (HiCross MS50 manufactured by Seiko Chemical Co., Ltd.)
[0324] • Antioxidant: Sumilizer GP manufactured by Sumitomo Chemical Co., Ltd.
[0325] <Example 1>
[0326] A thermoplastic elastomer composition was obtained by melt-blending 50 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene copolymer (B1-2-i), 20.9 parts by mass of ethylene-propylene copolymer (A-1-iv), 2.8 parts by mass of APO10-DL, 0.8 parts by mass of HiCross MS50, and 0.2 parts by mass of antioxidant in an upstream process of a twin-screw extruder at a barrel temperature of 200°C, followed by melt-blending 5 parts by mass of propylene polymer (A-2-i) in a downstream process of the twin-screw extruder at a barrel temperature of 200°C. The obtained thermoplastic elastomer composition was then injection molded using the method described in section 11 above to obtain a molded body. The physical properties of the molded body are shown in Table 1.
[0327] <Examples 2-5 and Comparative Examples 1-7>
[0328] Thermoplastic elastomer compositions were prepared in the same manner as in Example 1, according to the components and contents shown in Table 1. It should be noted that the amounts of antioxidants not listed in the table were the same as in Example 1.
[0329] The obtained thermoplastic elastomer composition was injection molded using the method described in section 11 above, thereby obtaining a molded article. The physical property test results of the molded article are shown in Table 1.
[0330]
[0331] Industrial practicality
[0332] According to the method for manufacturing the thermoplastic elastomer composition of the present invention, a thermoplastic elastomer composition capable of producing molded bodies with both excellent appearance and rigidity at a high level can be manufactured. Therefore, it is suitable for manufacturing molded bodies requiring excellent appearance and high rigidity, such as airbag housings, and has high applicability in various fields of industries such as automobiles and other transportation machinery, sports and leisure products, household products, electrical and electronic equipment, and construction.
Claims
1. A method for manufacturing a thermoplastic elastomer composition, wherein, The method for manufacturing the thermoplastic elastomer composition includes the following first and second steps, and the mineral oil (C) content in the manufactured thermoplastic elastomer composition is less than 5% by mass. First step: A step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of organic peroxides, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g; The second step: Further addition of polypropylene (A-2) and melt mixing, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C... cxis The value is above 1.5 dl / g and below 7 dl / g.
2. The method for manufacturing the thermoplastic elastomer composition according to claim 1, wherein, The second step is carried out under conditions where the organic peroxide is substantially absent.
3. The method for manufacturing the thermoplastic elastomer composition as described in claim 1 or 2, wherein, The same extruder with multiple feed ports is used in both the first and second processes, and polypropylene (A-2) is supplied from a feed port located further downstream.
4. The method for manufacturing the thermoplastic elastomer composition according to claim 1 or 2, wherein, In the second step, 0.1 to 15 parts by mass of polypropylene (A-2) are supplied relative to a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B).
5. The method for manufacturing the thermoplastic elastomer composition as described in claim 1 or 2, wherein, Based on a total of 100 parts by weight of polypropylene (A-1) and ethylene copolymer rubber (B), 30 to 70 parts by weight of polypropylene (A-1) and 70 to 30 parts by weight of ethylene copolymer rubber (B) are supplied.
6. The method for manufacturing the thermoplastic elastomer composition according to claim 1 or 2, wherein, At least a portion of the ethylene copolymer rubber (B) is an amorphous ethylene-α-olefin copolymer (B1-1) or an ethylene-α-olefin-non-conjugated diene copolymer (B1-2).
7. A thermoplastic elastomer composition, wherein, The thermoplastic elastomer composition is manufactured by a manufacturing method comprising the first and second steps described below, and the mineral oil (C) content in the thermoplastic elastomer composition is 5% by mass or less. First step: A step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of organic peroxides, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g; The second step: Further addition of polypropylene (A-2) and melt mixing, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C... cxis The value is above 1.5 dl / g and below 7 dl / g.
8. The thermoplastic elastomer composition of claim 7, wherein, The second step is carried out under conditions where the organic peroxide is substantially absent.
9. The thermoplastic elastomer composition of claim 7 or 8, wherein, The same extruder with multiple feed ports is used in both the first and second processes, and polypropylene (A-2) is supplied from a feed port located further downstream.
10. The thermoplastic elastomer composition of claim 7 or 8, wherein, In the second step, 0.1 to 15 parts by mass of polypropylene (A-2) are supplied relative to a total of 100 parts by mass of polypropylene (A-1) and ethylene copolymer rubber (B).
11. The thermoplastic elastomer composition of claim 7 or 8, wherein, Based on a total of 100 parts by weight of polypropylene (A-1) and ethylene copolymer rubber (B), 30 to 70 parts by weight of polypropylene (A-1) and 70 to 30 parts by weight of ethylene copolymer rubber (B) are supplied.
12. The thermoplastic elastomer composition of claim 7 or 8, wherein, At least a portion of the ethylene copolymer rubber (B) is an amorphous ethylene-α-olefin copolymer (B1-1) or an ethylene-α-olefin-non-conjugated diene copolymer (B1-2).
13. The thermoplastic elastomer composition of claim 7 or 8, wherein, The thermoplastic elastomer composition is used for injection molding.
14. The thermoplastic elastomer composition of claim 7 or 8, wherein, With a barrel temperature of 220℃, a mold temperature of 50℃, and an injection rate of 25cm, 3 The thermoplastic elastomer composition according to claim 7 or 8 is injection molded at a speed of / second to obtain a molded body with a width of 90 mm × length of 150 mm × thickness of 2.0 mm, and the flexural modulus of the molded body is measured according to JIS K7171 and is 330 MPa or more.
15. A molded body, wherein, The molded body comprises the thermoplastic elastomer composition according to any one of claims 7 to 14.
16. The molded article as claimed in claim 15, wherein, The flexural modulus of the molded body, as measured according to JIS K7171, is 330 MPa or higher.
17. The molded article as claimed in claim 15 or 16, wherein, The molded body is an uncoated molded body.
18. The molded article as claimed in claim 15 or 16, wherein, The molded body is an airbag containment cover.
19. A method for manufacturing a molded article containing a thermoplastic elastomer composition, wherein, The manufacturing method includes the steps of mixing and molding a thermoplastic elastomer composition precursor with polypropylene (A-2). The intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-2) at 20°C cxis The concentration is above 1.5 dl / g and below 7 dl / g. The thermoplastic elastomer composition precursor is manufactured by a manufacturing method comprising a step of melt-blending polypropylene (A-1) and ethylene copolymer rubber (B) in the presence of an organic peroxide, wherein the intrinsic viscosity [η] of the xylene-insoluble component of the polypropylene (A-1) at 20°C is... cxis ] Greater than or equal to 0.1 dl / g and less than 1.5 dl / g.
Citation Information
Patent Citations
Production of alpha-olefin polymer
JP1986218606A
Production of alpha-olefin polymer
JP1986287904A
Ethylene-propylene block copolymer
JP1993194685A
Catalyst for polymerizing alpha-olefin and production of alpha-olefin polymer
JP1995216017A
Propylene / ethylene-alpha-olefin block copolymer and its production
JP1997316147A